Coaching clinik meningkatkan kebugaran jasmani pada lanjut usia melalui aktivitas fisik di Yakes Telkom Area 7 Kepulauan - Hasyim Hasyim; Imam Imam; Silatulrahmi Silatulrahmi (Seminar Nasional Pengabdian Kepada Masyarakat, 2019)
The purpose of community service is to improve the physical fitness of the elderly (retirees) telkom area 7 telecommunications islands through coaching clinic through physical activity (sports) using fitness equipment. The solutions offered are: Improve physical fitness related to health such as lung heart endurance and strength training in elderly Telkom yakes area 7 islands. Through this Community Service activity, the types of results produced are: 1). Applying partners to the use of physical fitness equipment related to health such as endurance of the heart of the lungs and strength training 2) Guiding retirees to Telkom Area 7 islands increases motivation and health benefits for the elderly (retirees) in training. Health-related physical fitness includes aspects of physiological functions that offer prevention against disease as a result of a sedentary lifestyle. This can be enhanced and / or maintained through regular physical activity programs and based on the principles of correct practice. The components of physical fitness related to health according to Wahjoedi (2000: 59) include,